How to Teach Plate Movements Effectively? Key Results of an Educational Reconstruction of the Movement of Tectonic Plates - Conrad, Dominik (Journal of Geography Education, 2016)
The model of educational reconstruction was used in this study to develop educational guidelines for teaching plate movements. This is based on a comparison of the results of Scientific Clarification with students` conceptions identified by analyzing qualitative interviews. Many structures and processes concerning plate movements cannot be perceived directly and so, according to theory of experientialism, they can only be understood on an imaginary level. As a result, instructors teaching plate movements are required to use adequate metaphors from source domains which are clearly comprehensible. Appropriate source domains could be activated for example by language, gesture or analogies. The article focusses on key results of scientific clarification, a comparison between scientific and learners’ perspective and the development of educational guidelines for teaching plate tectonics.